Embrace 4 cultures and student solidarity in new MPP leadership - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 11 January 2021 - The newly appointed Students’ Representative Council (MPP), Universiti Malaysia Pahang (UMP) for the 2021/2022 session is recommended to pay serious attention to the fostering of a culture of wisdom, prosperity, respect, and love.